Apuntes histórico-arqueológicos en torno a la danza del Huacón - Barraza Lescano, Sergio (2009)
This article constitutes an attempt to document the origins of the «Huaconada,» a dance currently performed in the town of Mito (Mantaro Valley) but which, as can be inferred from archival sources, was widespread throughout the coast and central Andes of Peru during colonial times. The study of ethnohistorical sources from the sixteenth and seventeenth centuries reveals a relationship between the «huacones»and the ancestral founders of the communities where the dance was performed. This explains the repeated association of these mythical characters with elements connected to ancestor cults in the Andes, such as caves (machay) and «huancas». The analysis suggests the role of this type of ceremonies in the agricultural calendar of native indigenous populations during the colonial period.From the review of archaeological evidence, it is suggested that certain pieces of wood carving from prehispanic burial wrappings and masks incorporating human remains represent the materials used for paraphernalia that is employed in the dance.